Islamic Organizational Culture Moderates the Influence of Transformational Leadership Style on the Performance of Employees at Bank Syariah Indonesia KCP Kalianda - Verawati, Heni; Wulan, Mutiasari Nur (Al-Mashrof: Islamic Banking and Finance, 2024)
The purpose of this research is to examine the Islamic Organizational Culture in moderating the influence of transformational leadership style on employee performance. The research was conducted at Bank Syariah Indonesia KCP Kalianda, with data collection using questionnaires on a sample of 30 employees. The data analysis technique used is Moderated Regression Analysis (MRA) with SPSS software version 20. The results showed that transformational leadership style has a positive and significant effect on the performance of employees at Bank Syariah Indonesia KCP Kalianda. Furthermore, Islamic organizational culture can moderate the influence of transformational leadership style on employee performance with a positive and significant value, which strengthens the relationship between transformational leadership style and employee performance